Effects Of Business Upgrading Programs On Their Competitiveness: Systematic Review And Meta-Analysis - Theodory, Yana; Mbue Innocent, Ndoh (International Journal of Science, Technology & Management, 2022)
The advent of free trade subjects' businesses in underdeveloped countries and economies in transition to the challenges of competitiveness and competition. To overcome these constraints, upgrading programs have been adopted as public policy. This review aims to identify the impacts of programs on their competitiveness and analyze the relationship between the variables of said programs and their effects. Sixty-three studies (63) are identified from online databases with arithmetic means as follows: Hindawi, n = 36, 0.22%; Google Scholar, n=33, 0.20%; Scorpus, n=33, 0.20%; and Google search, n = 31, 0.19% with specific Search terms such as "upgrade program + business + impact." Articles were selected using inclusion / exclusion criteria applied first at the title and abstract level, then at the full article level Data extraction for this review was safely done in Microsoft Excel, in order to identify the action variables of said programs and the effects. Through the analysis of the dimensions that determine the structural competitiveness index (ICS) of the countries, was carried out to explain the contribution of the variables of the contextual environment, to the variables of the upgrading program and the effect of impact in terms of intensity on the observed effects. The effects identified relate to to the variables of the upgrading program and the effect of impact in terms of intensity on the observed effects. The effects identified relate to to the variables of the upgrading program and the effect of impact in terms of intensity on the observed effects. The effects identified relate to 8 indicators of positive effects grouped into: financial performance, economic performance, organizational performance, social and societal performance, with nuances on the macroeconomic impact due to the differences in the context of each country. Intensity of these effects does not translate in the same way, certainly because of the initial conditions for starting upgrading in each country, which takes into account the level of development, resource capital mobilized both human and financial and the level of importance of reforms, both structural and infrastructural carried out. The review highlights the merits of this public policy as a bulwark for companies in developing countries and economies in transition in a context of liberalization, faced with competition and competitiveness. It is pointed out that the success of this policy depends in particular on the capacity of the public authorities to implement a sound macroeconomic policy.